Narratives of John Pritchard, Pierre Chrysologue Pambrun, and Frederick Damien Heurter, respecting the aggressions of the North-West Company, against the Earl of Selkirk's settlement upon Red River [electronic resource]. - Pritchard, John, 1777-1856.; Pambrun, P. C. (Pierre Chrysologue), 1792-1841.; Heurter, F. D. (Frederick Damien) (London : John Murray ., 1819)
"Printed by J. Brettell . London"--T.p. verso and colophon. Electronic reproduction. Mode of access: Internet. 44